Proceedings of the 2nd International Conference on Automotive User Interfaces and Interactive Vehicular Applications 2010
DOI: 10.1145/1969773.1969796
|View full text |Cite
|
Sign up to set email alerts
|

Interaction weaknesses of personal navigation devices

Abstract: Automotive navigation systems, especially portable navigation devices (PNDs), are gaining popularity worldwide. Drivers increasingly rely on these devices to guide them to their destination. Some follow them almost blindly, with devastating consequences if the routing goes wrong. Wrong messages as well as superfluous and unnecessary messages can potentially reduce the credibility of those devices. We performed a comparative study with current PNDs from different vendors and market segments, in order to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…The projects in this research thread that most directly motivated our work are those of Hipp et al [18] and Brown and Laurier [6]. Both studies considered the "troubles" drivers encountered with in-car GPS devices in typical driving situations.…”
Section: Navigation Technologies In Standard Scenariosmentioning
confidence: 99%
See 2 more Smart Citations
“…The projects in this research thread that most directly motivated our work are those of Hipp et al [18] and Brown and Laurier [6]. Both studies considered the "troubles" drivers encountered with in-car GPS devices in typical driving situations.…”
Section: Navigation Technologies In Standard Scenariosmentioning
confidence: 99%
“…Both studies considered the "troubles" drivers encountered with in-car GPS devices in typical driving situations. Hipp et al [18] conducted a traditional user interface evaluation to compare the performances of different types of in-car navigation systems on the same route. They identified unexpressed routing preferences, failure to understand intentional detours from planned routes, and the lack of real-time traffic information as the common interaction weakness of commercial navigators (with the latter now being fixed in most modern navigation technologies).…”
Section: Navigation Technologies In Standard Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…Schreiber studied that the function of a map and its aesthetic perception heavily depend on the user's situational cognitive load [11]. Another research about navigation usability revealed that when using PNDs, wrong messages can potentially reduce the credibility of those devices [6]. Jensen suggested that different output configurations-audio, visual, and audiovisual-of a GPS system affect driving behavior and performance [7].…”
Section: Related Workmentioning
confidence: 99%
“…Recent research and studies show that the human mind can be distracted while driving and listening to the verbal route instructions or concentrating on the map that appear on the system's screen (Hipp et al, 2010). Such that the navigators do not pay attention to their immediate surrounding environment.…”
Section: Introductionmentioning
confidence: 99%